P-020 PERFORMANCE OF AN ATRAUMATIC AND VERSATILE LIGHT-ACTIVATED ADHESIVE FOR HERNIA MESH FIXATION. (13th October 2022) - Lopes, M; Bitton, E; Pereira, M; Dufresne, A; Guilbot, M
Abstract: Aim: This study evaluates the versatility and performance of a novel adhesive for atraumatic hernia mesh fixation. The TISSIUM adhesive is a biodegradable and biocompatible viscous liquid that can be precisely applied to different tissue and mesh.1 Once in place, the surgeon utilizes a light probe to polymerize the adhesive, creating a flexible elastomeric connection that provides strong, durable and atraumatic mesh fixation. Materials and Methods: The performance of the TISSIUM adhesive when used with a range of marketed mesh and against peritoneum (n=7) and muscle (n=3) was evaluated using a standardized lap-shear bench method using porcine tissues. The shear strength was compared to resorbable tacks (n=8) (against peritoneum as standard of care in IPOM) and self-adhesive meshes (n=4) and fibrin glue (n=3) (against muscle as classically used in the retromuscular approach). Results: Lap-shear data revealed that the TISSIUM adhesive performance was equivalent to resorbable tacks when fixing meshes to the peritoneum. Similar testing protocol demonstrated that the TISSIUM adhesive shear strength was 6 to 13 times superior to non- penetrating fixation devices such as fibrin glue or self-adhesive mesh. Conclusions: The use of the TISSIUM Adhesive for hernia mesh fixation is compatible with various mesh materials used in hernia repair and, in a bench model, outperforms existing non-penetrating methods in diverse tissue planes demonstrating the potential to help the surgeon achieve more effective and efficient atraumatic repair in a range of hernia procedures.